HYALINIZING TRABECULAR NEOPLASM OF THYROID - Riaz, Saima; Bashir, Humayun; Jahangir, Sidra; Nawaz, Muhammad Khalid (Journal of Ayub Medical College Abbottabad, 2014)
Hyalinizing trabecular neoplasm (HTN) is an uncommon, controversial lesion of thyroid. In its cytological and histopathological features, HTN mimics papillary and medullary carcinoma and usually misdiagnosed on fine needle aspiration cytology specimens. Pure HTN lesions are neoplams of very low malignant potential. Hemithyroidecomy is an adequate treatment; however, misinterpretation leads to total thyroidectomy and or followed by radioactive iodine ablation therapy. Correct histopathological diagnosis potentiates conservative management. We present a case in a 32-year-old female patient with review of diagnosis, management and one year follow up. Keywords: Hyalinizing trabecular neoplasm, thyroid, papillary, medullary